PENGARUH JOB INSECURITY, BEBAN KERJA DAN KOMPENSASI TERHADAP TURNOVER INTENTION KARYAWAN DI JNE DENPASAR UTARA - Ni Made Dwi Puspitawati; Ni Luh Gede Putu Purnawati; Ni Komang Suwartini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
High turnover can have a negative impact on the organization such as creating instability and uncertainty in the condition of the existing workforce and the high cost of HR management. This study aims to determine the effect of job insecurity, workload and compensation on employee turnover intention at JNE Denpasar Utara. This research was conducted at JNE Denpasar Utara. The population and sample in this study were North Denpasar JNE employees, totaling 40 people as research respondents. The method of determining the sample in this study is the saturated sampling method. Data was collected through documentation, interviews, and questionnaire methods. The data analysis technique used in this study is multiple linear regression analysis through the SPSS version 25 program. Based on the results of the analysis, this study shows that job insecurity has a positive and significant effect on employee turnover intention, which means that job insecurity increases, employee turnover intention at JNE Denpasar North increases. Workload has a positive and significant effect on employee turnover intention, which means that the better the workload, the employee's turnover intention at JNE Denpasar Utara will increase. Compensation has a positive and significant effect on employee turnover intention, which means that the better the compensation, the employee's turnover intention at JNE Denpasar Utara will increase.